Electiveness of game exercises in limited area to develop the some plan rule of football to youth - Asaad, Muafaq; Abedulqadeer, Mohammed (Journal of Physical Education, 2015)
Apply the game exercises in limited area to develop the some plan rule in football sample of research. to know the effectiveness of game exercises in limited areas on some plan rule (application) of football to research sample. The researcher used experiential program suit wigh nature of research problem and the sample of research choosen by delebrate method which represent (Anaa sport club and Haditha sport club) consist (40) players and exclude (8) players from the sample for different resonse for that the final collection is (32) players divided into two groups by boss one of them Experiential (Anaa club) and another adjusts (Haditha club) used (16) players for each group, the group of experiential applied experiential program (exercises play in limited areas); while the adjust After the Prt apply of belt for some plan rule applied the units of training on the experiential group in special application which contain (24) training units in (3) training units a week by use the high period stress the researcher conclude that the exercises application of game in limited areas by both methods of exercises high period stress(%80-%90) and frequency(%90-%100) after finish from main experiential a chieved the post and treated the results by suitable statistical means took part in develop the change of research understudy for sample research The recommendence of researcher: He recommend that the exercise of games in limited areas within experiential program during special some plan rule , which has active role in develop the aspects of physically , skillfully , plans and psychology